Pengaruh Citra Merek dan Kualitas Produk Terhadap Minat Beli Sepatu Merek Lokal di Sneakerzone Malang - Rifky Azka Fahreza; Farida Akbarina; Mohammad Maskan (Indo Publishing, 2025)
The growth of local shoe brands in Indonesia is increasing along with people’s awareness to support local products. Specs and Mills are two local brands that are now chosen by consumers who start to move from international brands. This research aims to find out the effect of brand image and product quality on buying interest of local shoes at SneakerZone Malang. study used descriptive statistics with 105 respondents. The data was collected through questionnaires and analyzed using SPSS 25 with validity test, reliability test, multiple linear regression, t-test, and F-test. The results show that brand image and product quality have a significant effect, both partially and simultaneously, with 65.1% contribution to buying interest. In conclusion, brand image and product quality are important factors that influence consumers to buy local shoes. Therefore, SneakerZone and local brands need to improve their marketing strategies and product quality to compete in the local market.